Evaluation of Relative Abundance and Perception of the Presence of Rock Pigeons Columba Livia (Columbiformes: Columbidae) at the National University of Costa Rica - Ramírez-Alán, Óscar (2017)
The presence of Columba livia dove in infrastructures leads to their deterioration. The increase of these birds in large cities has alarmed the population; the same situation occurs at the National University of Costa Rica premises. This study aimed to monitor the population due to its relative abundance. Five buildings within the university were selected, following the criterion of the presence of pigeons. Direct observation was conducted over a period of five months, three times a week. It was found that the west side of the Chemistry building is the most crowded (4.37 ± 1.17); the birds use spaces, such as air conditioners and holes on the roofs, as sites for nesting. 53% of the University workers interviewed disagreed in eradication processes. The availability of food resources and infrastructure are key factors to attract pigeons as these factors are ideal for nesting and roosting, which directly contributes to the growth of their populations. We recommend reducing artificial sites that can be used as perch, covering all the possible holes used for nesting, and educating people about potential problems that these pigeons can create.